Comparative Methylome Analysis of Campylobacter jejuni Strain YH002 Reveals a Putative Novel Motif and Diverse Epigenetic Regulations of Virulence Genes - Ghatak, Sandeep; Armstrong, Cheryl M.; Reed, Sue; He, Yiping (Frontiers in Microbiology, 2020)
Campylobacter jejuni is a major cause of foodborne gastroenteritis worldwide inflicting palpable socioeconomic costs. The ability of this pathogen to successfully infect its hosts is determined not only by the presence of specific virulence genes but also by the pathogen’s capacity to appropriately regulate those virulence genes. Therefore, DNA methylation can play a critical role in both aspects of this process because it serves as both a means to protect the integrity of the cellular DNA from invasion and as a mechanism to control transcriptional regulation within the cell. In the present study we report the comparative methylome data of C. jejuni YH002, a multidrug resistant strain isolated from retail beef liver. Investigation into the methylome identified a putative novel motif (CGCGA) of a type II restriction-modification (RM) system. Comparison of methylomes of the strain to well-studied C. jejuni strains highlighted non-uniform methylation patterns among the strains though the existence of the typical type I and type IV RM systems were also observed. Additional investigations into the existence of DNA methylation sites within gene promoters, which may ultimately result in altered levels of transcription, revealed several virulence genes putatively regulated using this mode of action. Of those identified, a flagella gene (flhB), a RNA polymerase sigma factor (rpoN), a capsular polysaccharide export protein (kpsD), and a multidrug efflux pump were highly notable.